1H high resolution magic-angle coil spinning (HR-MACS) μNMR metabolic profiling of whole Saccharomyces cervisiae cells: a demonstrative study - Wong, Alan; Boutin, Céline; Aguiar, Pedro M. (Frontiers in Chemistry, 2014)
The low sensitivity of Nuclear Magnetic Resonance (NMR) is its prime shortcoming compared to other analytical methods for metabolomic studies. It relies on large sample volume (30–50 µl for HR-MAS) for rich metabolic profiling, hindering high-throughput screening especially when the sample requires a labor-intensive preparation or is a sacred specimen. This is indeed the case for some living organisms. This study evaluates a 1H HR-MAS approach for metabolic profiling of small volume (250 nl) whole bacterial cells, Saccharomyces cervisiae, using an emerging micro-NMR technology: high-resolution magic-angle coil spinning (HR-MACS). As a demonstrative study for whole cells, we perform two independent metabolomics studies identifying the significant metabolites associated with osmotic stress and aging.